Estratégias de irrigação deficitária e uso de condicionador de solo na produção de tomate cereja em ambiente protegido - Silva, Daniela Andreska da (2024)
In view of the increase in areas subsisting water stress, the adoption of strategies aimed at increasing water productivity in irrigated agriculture becomes essential for water and food security. Furthermore, considering the low water retention of shallow sandy soils, the application of soil conditioners has shown to be a potential alternative in mitigating problems associated with irregular or deficient water availability. In view of this, the present study aims to evaluate the effects of the hydrogel as a water retainer in sandy soil with different irrigation strategies in the cherry tomato (Solanum lycopersicum) crop under protected cultivation conditions. The experimental design was in randomized blocks (DBC) with a 5x2 factorial scheme, referring to the five irrigation strategies (FI - full irrigation, RD - irrigation with continuous water deficit, E3 - irrigation with water deficit in the vegetative phase, E4 - irrigation with water deficit in the flowering and fruiting phase, E5 - irrigation with water deficit in the maturation and harvest phase), where in the treatments with water deficit, depths equivalent to 50% of the ETc were admitted. The second factor referred to the use of hydrogel® polymer (with hydrogel - CH, without hydrogel - SH), consisting of three plants per experimental plot, with four replications, totaling 40 experimental plots. The parameters analyzed in the research were: Growth (plant height, stem diameter, number of leaves, number of flowers, root length, leaf area, fresh matter of the leaf, stem and root, dry matter of the leaf, stem and root), production of cherry tomatoes (total number of fruits per experimental plot, total weight of fruits per treatment and transverse and longitudinal diameter of the fruits), physical chemical analysis of the fruit (color, total soluble solids, pH and total titratable acidity), gas exchange (photosynthesis net, transpiration rate, stomatal conductance, carbon dioxide concentration and leaf temperature), SPAD index, leaf water potential, water productivity in tomato and coefficient of sensitivity to water deficit. For productivity, the soil conditioning factor positively influenced only the RD treatment in the variables total number of fruits and total weight of fruits. Despite being subjected to water deficit, the E3 strategy showed a similar response to the control treatment, attributed to the best values for tomato productivity. Despite the highest water productivity (WP) averages being found in treatments without the use of hydrogel (FI, E4 and E5), the best response observed was when applying the E3 strategy in plants grown in pots with hydrogel. The highest values of sensitivity to water deficit were observed in treatments that suffered water deficit, especially in the flowering and fruiting phase (E4), with a slight reduction in the treatment with the presence of hydrogel. The results indicated "high sensitivity" in strategies E4 with hydrogel and RD, E4, E5 without hydrogel, (1.51; 1.69; 1.80 and 1.56, respectively), while for the "low sensitivity" status only strategies RD, E3, E5 with the use of the hydrogel and E3 without the use of the hydrogel were evidenced (0.63; -1.73, 0.18 and 0.59, respectively). The FI, E3 and E5 strategies provided greater gains in fruit production, with the last strategy determining the best fruit quality characteristics. The E3 and E5 strategy resulted in greater efficiency in water productivity in the cherry tomato crop. The RD’SH, E4’CH and E4’SH strategies should not be recommended for cherry tomato cultivation, given their greater sensitivity to water deficit and productivity. The use of the hydroretainer is only recommended in combination with the RD strategy.